2007
DOI: 10.1002/ca.20463
|View full text |Cite
|
Sign up to set email alerts
|

Relation of the external branch of the superior laryngeal nerve to the superior pole of the thyroid gland: An anatomical study

Abstract: The external branch of the superior laryngeal nerve (ELN) is intimately associated with the superior thyroid artery (STA) in relation to the superior pole of the thyroid gland, rendering it vulnerable to injury during the ligation of this vessel during thyroidectomy. Although most texts acknowledge the fact that the nerve is in close relation to the STA, there has not been an anatomical study to relate the position of the ELN to the superior pole of the thyroid gland. The aim of this study was to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
1
10
1
Order By: Relevance
“…Our results, which identified one case (0.99%) of ESLN at that location, are statistically comparable to those obtained by Naidoo 20 , who does not describe the nerve in that position at all. Thus, the results much differ from those published by Cernea 14 Therefore, based on those authors 12,14,18,19 , supported by the results obtained by them, the previous identification of the ESLN is recommended before the ligation of the superior thyroid artery in thyroidectomies, in order to prevent iatrogenic injuries.…”
Section: Results Results Results Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Our results, which identified one case (0.99%) of ESLN at that location, are statistically comparable to those obtained by Naidoo 20 , who does not describe the nerve in that position at all. Thus, the results much differ from those published by Cernea 14 Therefore, based on those authors 12,14,18,19 , supported by the results obtained by them, the previous identification of the ESLN is recommended before the ligation of the superior thyroid artery in thyroidectomies, in order to prevent iatrogenic injuries.…”
Section: Results Results Results Resultssupporting
confidence: 90%
“…However, because the differences between the findings by Cernea 12,14 , Furlan and Kierner 19 and the data obtained in the present study, as well as in Naidoo's 20 , are statistically significant and do matter in the context of a specific surgical decision -whether or not to identify the ESLN prior to the ligation of the superior thyroid artery -, it is necessary to take them into careful consideration.…”
Section: Results Results Results Resultscontrasting
confidence: 72%
“…In an anatomical review, Naidoo and co‐workers concluded that it is better to stay on the substance of the superior pole of the thyroid gland when ligating the superior thyroid artery, as the nerve is extremely close in relation to the superior pole of the normal thyroid gland . This is mainly relevant in Type 2 and 3 according to our proposed classification.…”
Section: Discussionmentioning
confidence: 84%
“…To prevent the ESLN from injury during neck surgery, investigators have made great efforts to determine its course in the neck and relations to the thyroid gland and superior thyroid artery. 21,22 However, little is known about the intramuscular branching of the ESLN within the CT muscle.…”
Section: Introductionmentioning
confidence: 99%